Đặc trưng cấu trúc và hoạt tính oxi hóa của xúc tác bismut molydat - Thắng và cộng sự, Lê Minh (Vietnam Journal of Chemistry, 2014)
Bismuth molybdate materials with various phases were synthesized by spray drying method. Their structural characteristics were studied by XRD and SEM, and surface area was determined using BET method. Catalytic characteristics were investigated toward oxidation reaction of propylene to acrolein. The results obtained show that the material samples obtained correspond to three almost pure phases of bismuth molybdate, alpha, beta and gamma. The reaction rates over beta and alpha phases are higher however; activated energy is lower on gamma phase. These data are in agreement with reaction schema of propylene oxidation, in which the abstraction of the first hydrogen atom proceeds over Bi-O polyhedron, while oxygen inserted into carbon atom in reactant molecule is derived from lattice bound to Mo.